2022
DOI: 10.3389/fpsyg.2022.821763
|View full text |Cite
|
Sign up to set email alerts
|

The Enactment of Classroom Justice Through Explicit Instruction: Deciphering the Changes in English as a Foreign Language Teachers’ Perceptions and Practices

Abstract: This mixed methods research study investigated if explicit instruction could affect EFL teachers’ perceptions and practices of classroom justice considering its three-dimensional conceptualization based on the social psychology theories of justice, encompassing the distributive, interactional, and procedural justice. To this end, 77 Iranian English as a Foreign Language (EFL) teachers, chosen through maximum variation sampling, attended a four-session online justice-training course. The data were collected bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Moreover, the research findings uncovered that the majority of the participants approved the necessity of receiving training on the rudimental aspects of teacher classroom justice for Iranian EFL teachers. This finding is in line with the results of other studies, which indicated that implicit or explicit increasing of teachers' knowledge and awareness of justice dimensions or principles could positively influence their justice perceptions and practices (Estaji & Zhaleh, 2022b;Kobs et al, 2021;Sonnleitner & Kovacs, 2020). The participants of this study explained that such trainings are essential because the teachers' just behavior in the classroom associates with improving the teacher-student relationships and increasing the students' meaningful learning, class participation, more focusing on academic goals, and interest in teacher and subject matter.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the research findings uncovered that the majority of the participants approved the necessity of receiving training on the rudimental aspects of teacher classroom justice for Iranian EFL teachers. This finding is in line with the results of other studies, which indicated that implicit or explicit increasing of teachers' knowledge and awareness of justice dimensions or principles could positively influence their justice perceptions and practices (Estaji & Zhaleh, 2022b;Kobs et al, 2021;Sonnleitner & Kovacs, 2020). The participants of this study explained that such trainings are essential because the teachers' just behavior in the classroom associates with improving the teacher-student relationships and increasing the students' meaningful learning, class participation, more focusing on academic goals, and interest in teacher and subject matter.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, the quantitative studies on classroom justice drastically outnumbered the few recent qualitative studies, which attempted to obtain rich, descriptive, and textual accounts of justice from their participants' perspectives. For instance, Chory et al (2017Chory et al ( , 2022, Estaji and Zhaleh (2021a, 2021b, 2022a, 2022b, Horan et al (2010), and employed open-ended justice questionnaires allowing the participants to explicate their responses to the extent that they desired. On the contrary to the majority of studies in the literature, which were mainly psychometrically-driven, these qualitative studies engaged in the content and thematic analyses of the obtained textual data and calculated frequencies only where needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have also used the procedural, distribute, and interactional justice. For example, Estaji and Zhaleh (2021) examined the viewpoints of 31 Iranian language teachers working in private language institutes. Their analysis revealed that while the teachers had different perspectives on classroom fairness, they emphasized the importance of distributive justice (equality, equity, and need), procedural justice (bias suppression, consistency, and voice), and interactional justice (exceptionally caring) in their understanding.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…The principles of equity, need, and equality are used to realize this facet (Jasso et al, 2016 ). This facet is thought to be maintained when learners perceive that the distribution of outcomes is based on their academic endeavors, contributions, and performance (Cropanzano et al, 2015 ; Ehrhardt et al, 2016 ; Estaji and Zhaleh, 2022 ). The second facet of classroom justice, interactional justice, refers to “to perceptions of fairness in the interpersonal treatment received by individuals, mainly as far as the communicative and relational requests that learners address to their teachers are concerned” (Berti et al, 2010 , p. 543).…”
Section: Introductionmentioning
confidence: 99%